The relationship between occupational noise exposure and hypertension using nearest age-matching method in South Korea male workers - Kim, Min Gi; Ahn, Yeon-Soon (Cogent engineering, 2021)
There is no consensus as to whether exposure to noise causes HTN. The objective of this study was to investigate the relationships between occupational noise exposure, pre- HyperTensioN (HTN) and HTN. The study subjects consisted of 107,407 workers who underwent annual special medical check-ups for workers from 2000 to 2004. The control group was an annual medical check-up cohort consisting of 152,790 workers examined over the same time period. The 1:1 nearest age matching of the two groups was done and multivariable logistic regressions were used to evaluate the effects of occupational noise on pre-HTN and HTN. The adjusted odds ratio (OR) of pre-HTN (OR 1.29, 95% CI 1.27-1.32) in noise-exposed workers was significantly higher than that in non-noised exposed workers. The adjusted OR of HTN (OR 1.42, 95% CI 1.38-1.45) in noise-exposed workers was significantly higher than that in non-noised exposed workers. According to this study, occupational noise exposure might be related to pre HTN and HTN.